Effect of long-term water immersion on the fracture toughness of denture base and reline resins - Finoti, Livia Sertori [UNESP]; Machado, Ana Lucia [UNESP]; Lima Chaves, Carolina de Andrade [UNESP]; Pavarina, Ana Claudia [UNESP]; Vergani, Carlos Eduardo [UNESP] (Wiley-Blackwell, 2012)
purpose: This study evaluated the fracture toughness (FT) of one denture base (Lucitone 550 - L) and four hard reline resins [Ufi Gel Hard (UH), Tokuyama Rebase II (TR), New Truliner (NT) and Kooliner (K)], and the effect of long-term water storage on this property.Materials and methods: Forty specimens (40 x 8 x 4 mm) of each material were made, and FT was assessed after polymerisation (control of reliners), after 48 +/- 2 h in water at 37 degrees C (control of denture base resin) and after storage in water at 37 degrees C for 7, 90 or 180 days (all materials). Data (MPa. m(1/2)) were analysed by two-way ANOVA and Games-Howell test (p = 0.05).Results: Resin L exhibited the highest FT mean values. After 180 days of storage, FT mean values of L (3.37), UH (1.53) and K (1.20) were higher than those of the other periods. FT mean values of NT decreased from control (1.63) to 7 days (1.30) and then remained constant. FT mean values of TR (1.13) were similar in all periods of analysis.Conclusion: The denture base resin L showed higher FT mean values than the reline resins. Long-term water storage increased the FT of L, UH and K, reduced the FT of NT and did not influence the FT of TR.
Keywords: acrylic resin; water storage; mechanical properties; toughness